An assessment of improving the sustainable agro-touristic offer in an emerging country using the integrative approach based on fuzzy logic - Puška, Adis; Nedeljković, Miroslav; Jeločnik, Marko; Subić, Jonel; Nancu, Dumitru; Andrei, Jean Vasile (Frontiers in Environmental Science, 2022)
The process of improving tourism requires prior determination of the existing offer, as well as assessment of the advantages and weaknesses of the given offer. Upon the analysis, it is possible to improve the tourist offer. This study examined ways in which agro-tourism can be improved, related to the foundation of sustainability. Methodologically, this article involves the use of expert assessment, additionally supported with fuzzy logic based on the fuzzy PIPRECIA and fuzzy MARCOS methods. Using the fuzzy PIPRECIA method, the criteria and sub-criteria were weighted, while the observed agro-tourism facilities in Bosnia and Herzegovina (BiH) were ranked according to the applied fuzzy MARCOS method. The results of the application of the fuzzy PIPRECIA method showed that for experts the most important are economic criteria, then environmental, and the latter important are social criteria. The most important sub-criterion is the quality of services. Out of the six facilities in question, the most appropriate results are achieved at the “Šadrvan” rural household, while the worst outcome is exhibited at the agro-tourism facility, (rural household) “Kovačević.” Sensitivity analysis confirmed these results. The aim of this article was to evaluate the agritourism offer in BiH, taking into consideration these six agritourism facilities. Based on that, it is necessary to determine on what advantages to build agritourism in BiH, and what should be corrected in order to be more competitive. Based on the obtained results, the facilities management should determine which sustainability criteria would need to be improved, as well as on which criteria it is desirable to build a competitive advantage, aiming to advance the tourist offer.